1965
DOI: 10.2307/1934873
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns of Some Native Annual and Perennial Herbs in Southern Wisconsin

Abstract: Temporal growth patterns and adaptive characters were studied in 17 perennial, 16 annual, and 4 biennial native herbs for one to three growing seasons in dry—mesic, mesic, and wet—mesic forest and in open barrens in southern Wisconsin. In annuals almost all dry matter produced was retained in aerial organs following the initial growth period. Below—ground weight increased rapidly in early season and then slowly increased or declined. In perennials there was a predominantly upward weight movement during growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 24 publications
3
74
0
1
Order By: Relevance
“…We propose that mortality as a result of intraspecific competition, e.g., for water, may be a significant density-dependent factor. Indeed, our experiment on water stress showed that seedlings and juveniles are sensitive to water stress (see also Struik and Curtis, 1962;Struik, 1965). According to our observations and those of Smith (1983a), Floerkea's root system is limited to the top 3-5 cm of the soil and does not extend horizontally beyond ϳ2-3 cm from the plant.…”
Section: Plant Survival and Reproduction-most Likely A Results Ofsupporting
confidence: 65%
See 4 more Smart Citations
“…We propose that mortality as a result of intraspecific competition, e.g., for water, may be a significant density-dependent factor. Indeed, our experiment on water stress showed that seedlings and juveniles are sensitive to water stress (see also Struik and Curtis, 1962;Struik, 1965). According to our observations and those of Smith (1983a), Floerkea's root system is limited to the top 3-5 cm of the soil and does not extend horizontally beyond ϳ2-3 cm from the plant.…”
Section: Plant Survival and Reproduction-most Likely A Results Ofsupporting
confidence: 65%
“…Successful Floerkea plants produce an average of only four mature nutlets each (Struik and Curtis, 1962; this study). In other annual species often associated with Floerkea, such as Collinsia verna and Galium aparine (ϳ20 seeds/plant), and Impatiens capensis and I. pallida (ϳ40 seeds/plant), the lack of a long-term persistent seed bank appears to be compensated for by a somewhat larger reproductive output (Struik and Curtis, 1962;Leck, 1979;Kalisz, 1991). The absence of a persistent seed bank and the low reproductive output of Floerkea appear to be compensated for by a high survival of the seeds from dispersal to emergence.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations